INFLUENCE OF SULFATE ION ENVIRONMENT ON THE CEMENT MATRIX MODIFIED BY REDISPERSIBLE POLYMERS - KOVALENKO, YURII; TOKARCHUK, VOLODYMYR; KOVALEKO, SVITLANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Injection of sulfate ions into the cement matrix with water by wet spraying due to high moist in the environment is the reason of the deterioration acceleration and durability decrease with time. The effects of introduction of redispersible polymers (RP) and calcium formate on the increasing of the durability and decreasing of the deterioration effect caused by sulfate ions on the cement matrix were studied. Vinyl-acetate/versatate, vinyl-acrylic copolymer and calcium formate were mixed into nine separate cement mixtures at a concentration of additives 1 %, 3 % and 5 % respectively. Three different sulfate ion environment were sprayed through the fog environment at high moist concentration using a salt spray device “Salt Fog Chamber”. Test results showed that different additive in different sulfate environment has various affects both on the deceleration of the structure deterioration and the reduction of the strength of cement matrix. Vinyl-acetate/versatate and calcium formate in concentrations of 1% and 3% have high stability while maintaining strength at the level of exploitational properties of the matrix. While, vinyl-acrylic copolymer at 5 % has more resistance to strength loss after 168 days of withholding in an aggressive environment compared to 1 % and 3 %. Detailed observation of the structure formation of the cement matrix at 168 days shows formation that relate both to the hydrated cement minerals and complexes of organic salts. This formation allowed at the late age of the experiment to decrease the strength loss under intensive impact of SO42– migration through the matrix due to the encapsulating of cement minerals at early ages of hydration in polymer films with RP and active early formation of Ca(OH)2 for formate. This allowed the cement matrix to retain its shape for a long periods, become more stable, reduce the washing out of soluble cement components at early ages, and reduce the content of active Ca by bonding it into semisoluble compositions that cause the decreasing of the negative effect on cement matrix by SO42–.
Keywords: portland cement; dry ready-mixes; redispersable powders; calcium formate; corrosion resistance